ANALYSIS OF LITERACY EVENTS IN THE CITY OF CORUMBÁ DE GOIÁS START OF THE CAMINHO DE CORA TRAIL ROUTE (CIPEEX, 2024)
LITERACY EVENTS CONTRIBUTE TO THE DEVELOPMENT OF CHILDREN THROUGHOUT THEIR SCHOOL LIFE, BEING LED BY TEACHERS, CURRICULA, AND SCHOOL. THE SCHOOL IS AN INTENTIONAL ENVIRONMENT FOR ACADEMIC, SOCIAL, AND CULTURAL SOCIALIZATION PRACTICES.SCHOOL IS A PLACE WHERE CHILDREN HAVE ACCESS TO A VARIETY OF EDUCATIONAL RESOURCES, SUCH AS BOOKS, TEACHING MATERIALS, TECHNOLOGIES, AND SPECIALIZED TEACHERS.IN THE PROCESS OF EVERYDAY SCHOOL LIFE, THE TEACHER IS THE DRIVER OF TEACHING BECAUSE HE HAS A BETTER UNDERSTANDING OF HUMAN DEVELOPMENT AND SCHOOL LITERACY ISSUES. SPECIALIZED PROFESSIONAL KNOWLEDGE ABOUT TEACHING AND LEARNING MAKES HIM A HIGH-IMPACT AGENT ON DIFFERENT APPROACHES PERSPECTIVES INSIDE THE CLASSROOM WITH THE AIM OF TRAINING PEOPLE TO OFFER STUDENTS A MORE INCLUSIVE AND DIVERSE EDUCATION IN THE GLOBALIZED WORLD.THE TEACHER CAN SEEK A MORE IN-DEPTH UNDERSTANDING OF ISSUES RELATED TO COLONIALITY-DECOLONIALITY, POWER STRUCTURES, CULTURAL DIVERSITY, AND INCLUSION. THIS INVOLVES TARGETING EDUCATION AROUND DIFFERENT DECOLONIAL PERSPECTIVES AND APPROACHES, AS WELL AS CHALLENGING THE TRADITIONAL EUROCENTRIC CURRICULUM.BY EXPANDING THEIR KNOWLEDGE, THE TEACHER WILL BE BETTER PREPARED TO OFFER A MORE INCLUSIVE AND DIVERSE EDUCATION THAT VALUES HISTORY AND CULTURE AND THUS AWAKEN LOCAL EMPOWERMENT.LANGUAGE EDUCATION PROVIDES CHILDREN WITH THE DEVELOPMENT OF COMMUNICATION SKILLS AND ATTITUDES, SUCH AS READING, WRITING, AND SPEAKING. THESE SKILLS ALLOW CHILDREN TO EXPRESS THEMSELVES, SHARE THEIR IDEAS, THOUGHTS, AND EMOTIONS EFFECTIVELY, STRENGTHENING THEIR SELF-CONFIDENCE, ABILITY TO MAKE THEMSELVES HEARD, AND RESPECT OTHERS. PROMOTE A MORE INCLUSIVE, CRITICAL EDUCATION THAT VALUES DIVERSITY OF PERSPECTIVES AND KNOWLEDGE.THE CITY OF CORUMBÁ DE GOIÁS IS LOCATED 1110 KM FROM THE CAPITAL OF GOIÂNIA. IT IS A CITY IN THE INTERIOR OF GOIÁS WITH A POPULATION OF APPROXIMATELY 11,223 PEOPLE (IBGE, 2021), WHERE THE MAJORITY RESIDES IN RURAL AREAS. THEY HAVE GREAT TOURIST ATTRACTIONS DUE TO NATURAL BEAUTY SUCH AS RIVERS AND WATERFALLS. TODAY, IT IS THE GROUND ZERO OF THE TRAIL CALLED CORA CORALINA, WHICH RECEIVES PILGRIM TOURISTS ON FOOT OR BY BICYCLE FROM VARIOUS PARTS OF THE COUNTRY AND THE WORLD TO GET TO KNOW THE CULTURE AND BEAUTY OF THE INTERIOR OF THE STATE OF GOIÁS UP CLOSE.THE CITY'S VISIBILITY HAS INCREASED IN RECENT YEARS, MAINLY BECAUSE IT IS NAMED AFTER THE FAMOUS GOIÁS POET CORA CORALINA WHO LIVED IN THE INTERIOR OF THE STATE OF GOIÁS. GIVEN THIS INFORMATION, THE TOPIC AROUSES CURIOSITY TO KNOW WHETHER SCHOOL INSTITUTIONS IN THE CITY ARE ALSO INVOLVED IN THIS PROCESS OF VALUING AND DISSEMINATING LOCAL CULTURE.